Meaning making: examining Malay adolescents’ media text decoding process in constructing cultural identity - Sabariah Mohamed Salleh,; Bauer, Thomas A. (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper illustrates how meanings from television are negotiated and used in adolescents’ construction of meaning, focussing on cultural identity. This article is not an attempt to generalize Malaysian audiences but aims to explore the process of making meanings and understand the process of negotiations young Malaysians go through from watching television in relations to the construction of their cultural identity. Four focus group interviews were held with groups, which are made up of two different socio-economic background, which consist of urban and adolescents living in a big city, and adolescents living in a rural, small town. It was discovered that the activities, which revolves around their engagement with television, plays a part in their construction of meaning. Although studies in activities in the process of meaning making has been quantitative and used to measure effects of watching television, the qualitative approach has provided an additional insight, in which, the activities can be used to explain the inputs or element which assisted these adolescents in their process of engagement with television text. Several activities have been identified which are prominent in the process of engagement with television texts. These include intentionality, selectivity, utilitarianism and orality and these activities are considered as influencing the process of making meanings of television texts.